Power saving MAC protocols in wireless sensor networks: a performance assessment analysis - Cotrim, Rafael (2021)
Wireless sensor networks are an emerging technology that is used to monitor points or objects of interest in an area. Despite its many applications, this kind of network is often limited by the fact that it is difficult to provide energy to the nodes continuously, forcing the use of batteries, which restricts its operations. Network density may also lead to other problems. Sparse networks require stronger transmissions and have little redundancy while dense networks increase the chances of overhearing and interference. To address these problems, many novel medium access control (MAC) protocols have been developed through the years. The objective of this study is to assess the effectiveness of the T-MAC, B-MAC, and RI-MAC protocols in a variable density network used to collect data inside freight trucks carrying fruits that perish quickly. This article is part of the PrunusPós project, which aims to increase the efficiency of peach and cherry farming in Portugal. The comparison was done using the OMNET++ simulation framework. Our analysis covers the behavior and energetic properties of these protocols as the density of the network increases and shows that RI-MAC is more adaptable and consumes less energy than the alternatives.